Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s12955-017-0726-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new Rasch-based scoring algorithm for the National Eye Institute Visual Functioning Questionnaire to improve its interpretability

Abstract: BackgroundThe NEI VFQ-25 has undergone psychometric evaluation in patients with varying ocular conditions and the general population. However, important limitations which may affect the interpretation of clinical trial results have been previously identified, such as concerns with reliability and validity. The purpose of this study was to evaluate the National Eye Institute Visual Functioning Questionnaire (NEI VFQ­25) and make recommendations for a revised scoring structure, with a view to improving its psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“… 15–17 Scores from all questionnaires were calculated for each DED severity group; scores from the NEI VFQ-25 were calculated using the new 28-item revised VFQ (VFQ-28R) scoring. 18 …”
Section: Methodsmentioning
confidence: 99%
“… 15–17 Scores from all questionnaires were calculated for each DED severity group; scores from the NEI VFQ-25 were calculated using the new 28-item revised VFQ (VFQ-28R) scoring. 18 …”
Section: Methodsmentioning
confidence: 99%
“…2001) as well as item response theory using Rasch analysis (Petrillo et al. 2017) when applicable. The Mann–Whitney U ‐test was used to compare the QoL data and the BCVA data between the FASD group and controls.…”
Section: Methodsmentioning
confidence: 99%
“…Rasch analyses and Item Response Theory are relatively new analyses used to develop, evaluate and improve patient reported outcomes. They might have been relevant in current study, to both evaluate and potentially suggest improvement in items of NEI-VFQ 25 as an previous study has shown in the same population [49]. However, the aim in the present study was not such an extensive evaluation, but rather to validate the original measure in a Norwegian population with nAMD.…”
Section: Discussionmentioning
confidence: 93%